Pharmacological treatment of attention-deficit/hyperactivity disorder: assessing outcomes. Issue 4 (July 2015) - Adamo, Nicoletta; Seth, Sarah; Coghill, David
<x xml:space="preserve">Abstract</x> A substantial body of evidence has supported the efficacy and safety of pharmacological treatment available for attention deficit/hyperactivity disorder (ADHD). There is increasing agreement that the important treatment outcomes for ADHD extend beyond improvement in core symptoms and that a more generic (or global) concept of remission is the overarching goal of treatment. However, there is no consensus on the best definition of remission or on how best to conceptualize and measure broader treatment outcomes. In this article, we provide an overview of the various methods and approaches to measuring treatment outcomes for ADHD with respect to symptoms, impairment, quality of life, adverse events and safety as well as cognition. We will describe the ways that they may be used within routine clinical practice and think ahead about the kinds of studies that are required to move the field forward.